Surface properties and catalytic behavior of Ru supported on composite La2O3-SiO2 oxides - Faroldi, Betina María Cecilia (2009)
Binary La2O3-SiO2 supports were employed to obtain active, stable Ru catalysts with high dispersions for the dry reforming of methane. Supports with 15, 27, 40 and 50 wt. % of La2O3 were prepared by incipient wetness impregnation on SiO2. The Ru loading was 0.6 wt % for all catalysts. The solids were evaluated in a fixed-bed reactor under differential conditions. Previously, they were reduced at either 673 K or 823 K. The most active catalyst was Ru/La2O3(50)-SiO2. All the uncalcined formulations were stable after 100 hours on stream. XRD, CO chemisorption, TPR, XPS, ISS and CO adsorption monitored by FTIR were employed to characterize the catalysts and the Ru species. XRD showed the presence of La2Si2O7 with low crystallinity in all the supports. By means of XPS and ISS, the formation of a surface La2Si2O7 phase was suggested for samples containing La2O3 up to 40 wt. %. Higher contents could lead to surface La2O3 particle growth. The TOFCH4 values showed a minimum for the Ru/La2O3(40)-SiO2 solid in agreement with a lower metal-support interaction. The Ru/La2O3(50)-SiO2 catalyst exhibited the highest TOFCH4 for both reduction treatments. The differences in thermal stability of the CO adsorbed species on Ru supported on silica or on binary La2O3-SiO2 supports sustain that the presence of lanthanum influences the metal support-interaction and metal dispersion.